Icons for Software Implementations of Interactive Multiobjective Optimization Methods: A Semantic Distance Study - Silvennoinen, Johanna; Lárraga Maldonado, Giomara; Ruiz-Mora, Ana Belén; Ruiz-de-la-Rúa, Francisco; Misitano, Giovanni; Miettinen, Kaisa (Wiley, 2025)
Multiobjective optimization problems involve several conflicting objective functions to be optimised simultaneously and solu-tions to these problems represent different trade-offs. When applying interactive methods, a decision maker with domain exper-tise provides one's preference information over several iterations, according to which new solutions are computed until finding asolution with the most preferred trade-offs. Publications on interactive multiobjective optimization methods mainly focus on theoptimisation algorithm, and little attention is paid to their implementations, not to mention the development of user interfacesthat enable interaction with the decision maker. User interfaces involve icons but there are no studies about icons for the specificfunctionalities of multiobjective optimization methods. Icons convey meaning effectively to users interacting with technology.With these small pictorial representations, information on system functionalities is communicated quickly. However, the imme-diacy of icon recognition can also lead to misunderstandings and difficulties in using the system if they are not designed properly.Semantic distance in icon design indicates the closeness of the pictorial representation to its intended functionality and, thus,functions as the main principle in designing effective icons. An empirical study (N = 38) was conducted to examine the semanticdistances of icons for interactive multiobjective optimization methods implemented in an open-source software framework. Thestudy addressed the main functionalities. According to our main findings, we suggest an icon set for the considered functionali-ties, to enable fluent interaction with decision makers and other involved parties utilising interactive multiobjective optimizationmethods via user interfaces.
Keywords: Toma de decisiones; Optimización matemática; Signos y símbolos; Interfaces de usuario; Decision making; Icon design; Interactive methods; Multiple criteria optimization; User interfaces